ANALISIS VOLUME PERDAGANGAN SAHAM DAN ABNORMAL RETURN SEBELUM DAN SESUDAH PEMECAHAN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - RATIH NIDIA, RR. (Jurnal Akuntansi AKUNESA, 2014)
This study examines whether there is a difference of Stocks Trading Volume and Abnormal Return around the split announcement for 21 days including the day of the stock split announcement. The sample of this study is the companies that split shares listed on the Indonesia Stock Exchange from 2011 to 2013 after the qualified purposive sampling that amounts to 26 companies. The data analysis technique used hypothesis testing with t- test methods. The volume reactions were examined by use of the average trading volume activity (ATVA) and for abnormal return used of average abnormal return (AAR).The results showed that there are difference in average trading volume activity (ATVA) before and after the stock split with a significance value 0,002, then H0 refused and H1 accepted, even ATVA after stock split is lower than before stock split. That has possibility because semi strong efficient market was absorbing information quickly as bad news. The test results of average abnormal return (AAR) was different from the results of ATVA, where there is no significant AAR before and after stock split with a significance value 0.849, then H0 accepted and refused H2. Thus result support semi-strong efficiency market, whereby it is not possible to earn abnormal return in the Indonesia Stock Exchange.Keywords: Stock split, trading volume activity, abnormal return, t-test